2010
DOI: 10.1890/09-0853.1
|View full text |Cite
|
Sign up to set email alerts
|

Applications of particle image velocimetry for seed release studies

Abstract: Nonrandom seed release is an important determinant of how far seeds disperse, but the mechanisms that promote wind-related seed release under varying atmospheric conditions are poorly understood. We explored the use of particle image velocimetry (PIV) to gain a better mechanistic understanding of seed release by visualizing the flow velocities and vorticity in a two-dimensional slice of air around inflorescences. Pilot data taken in a wind tunnel show gradients in air velocity at the top of Carduus nutans capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Another non-exclusive explanation would be that both types of spores are not dispersed at the same period of the day as reported previously [61]. Recent studies have demonstrated the importance of the conditions at release on the dispersal pattern eventually realized [83][86]. Further developments in this way will surely improve our understanding of the M. fijiensis system.…”
Section: Discussionmentioning
confidence: 75%
“…Another non-exclusive explanation would be that both types of spores are not dispersed at the same period of the day as reported previously [61]. Recent studies have demonstrated the importance of the conditions at release on the dispersal pattern eventually realized [83][86]. Further developments in this way will surely improve our understanding of the M. fijiensis system.…”
Section: Discussionmentioning
confidence: 75%
“…Additionally, the pre‐seed release capitulum is known to interact with both laminar and turbulent air flows to create high vorticity, and potentially lift, over the top and centre of capitula (Marchetto et al . ). The new results presented here indicate that seeds from the centre of the capitulum require less force for removal and, when exposed to slow winds, are predicted to disperse longer distances than other seeds from the same capitulum.…”
Section: Discussionmentioning
confidence: 97%
“…Spatiotemporal fluctuations in model behavior can help to optimize the placement and monitoring designs for seed traps; for example, by proposing a more detailed sampling design in areas where seed deposition is expected to vary along steep spatial gradients (e.g., across canopy gaps or other landscape transitions) or during periods when more LDD is expected. Conversely, the degree of nonrandomness of seed abscission needs to be quantified empirically (e.g., Wright et al 2008;Marchetto et al 2010), and the corresponding dispersal kernel measured, so that models can predict LDD under appropriately filtered wind conditions. Ultimately a true understanding of dispersal will require continual bi-directional interplay between models and data, between theory and reality.…”
Section: Future Directionsmentioning
confidence: 99%